[PP.08.13] EFFECTS OF MULTIELECTRODE RENAL DENERVATION ON SYMPATHETIC NERVE ACTIVITY AND INSULIN RESISTANCE IN METABOLIC SYNDROME. (September 2017) - Dimitriadis, K.; Tsioufis, K.; Kasiakogias, A.; Kalos, Th.; Liatakis, G.; Nikolopoulou, L.; Koutra, E.; Konstantinidis, D.; Andrikou, E.; Tousoulis, D.
Abstract : Objective: This study aimed to investigate the effects of renal denervation (RDN) on sympathetic nerve activity and insulin resistance in patients with metabolic syndrome at 3 months post-RDN. Design and method: Seventeen patients fulfilledat least 4/5 criteria for metabolic syndrome and under stable use of at least two anti-hypertensive drugs at maximum tolerated doses for at least 4 weeks were enrolled and randomized in 3:1 ratio to RDN [n = 13, 12 males, age: 58 ± 7 years] and Control groups [n = 4, 3 males, age: 60 ± 5 years]. Both groups were followed up for 3 months. Muscle sympathetic nerve activity (MSNA)measurements were performed to assess sympathetic nerve activityat fasting state and during standard 75 g oral glucose tolerance test (OGTT). Blood sampling was also performed to assess insulin resistance (HOMA-IR). Results: In the RDN group, office BP reduced by 16 ± 21/10 ± 11 mmHg (P = 0.01/0.007); average 24-hour BP reduced by 14 ± 16/5 ± 8 mmHg (P = 0.008/0.03); waist circumference reduced by 3.1 ± 3.6 cm (P = 0.008);and MSNA at fasting state reduced from 55 ± 9 bursts per minute/82 ± 15 bursts per 100 heart beats to 46 ± 8 bursts per minute/71 ± 15 bursts per 100 heart beats (P = 0.0008/0.006) at 3 months post-RDN. During OGTT, while blunted MSNA responseswere notedat baseline throughout the 120-minute test (P > 0.05/0.05vs. MSNA at fasting state), improved MSNA responses with burst frequency/burst incidence increased to 52 ± 8 bursts per minute/76 ± 12 bursts per 100 heart beats (P < 0.001/0.04 vs. the MSNA at fasting state, n = 13) at 30 minutes and to58 ± 16 bursts per minute/80 ± 14 bursts per 100 heart beats (P = 0.004/0.008 vs. the MSNA at fasting state, n = 10) at 120 minutes were observed at 3 months post-RDN. No such improvements were observed in the 4 control group subjects at 3 months follow-up. No statistical significant change was observed in the HOMA-IR in both groups at 3 months. Conclusions: In this pilot study of patients with metabolic syndrome and associated hypertension, RDN reduced elevated sympathetic nerve activity and restored the normal neural response to oral glucose loading. Strategies to target specifically the elevated sympathetic nerve activity may provide substantial clinical benefits in this setting.